Improving Fraction Mathematics Learning Outcomes through Education Realistic Mathematics in Grade IV Students: Meningkatkan Hasil Belajar Matematika Materi Pecahan melalui Pendidikan Matematika Realistik pada Siswa Kelas IV - sri susanti (Perkumpulan Doktor Indonesia Maju (PDIM), 2020)
This study aims to improve the mathematics learning outcomes of fraction material through realistic mathematics education in grade IV.C SD Negeri 08 Pulau Punjung. The research design was carried out in two cycles consisting of planning, implementing, observing, and reflecting. The research subjects were students of grade IV.C SD Negeri 08 Pulau Punjung with a total of 25 students consisting of 13 girls and 12 boys. The object of research is the result of learning mathematics in fractions. Data collection techniques using observation and tests. The research data were analyzed using quantitative descriptive techniques to analyze test results and observation sheets. The results showed that the application of Realistic Mathematics Education could improve the learning outcomes of grade IV.C students of SD Negeri 08 Pulau Punjung with regard to fraction material. This was shown by the increase in the results of the class average score of students in the first cycle stage was 69.4 and the second cycle stage increased to 84.4, an increase of 15 points. Based on the data on student mathematics learning outcomes, the learning completeness in the first cycle stage was 40% (Poor Category) and increased to 92% (Special Category) in cycle II.